Diminazene aceturate attenuates hepatic ischemia/reperfusion injury in mice - So Hye Yoon; Hye Bin Kang; Jongwan Kim; Keunje Yoo; Sang Jun Han (Scientific Reports, 2022)
Abstract Hepatic ischemia/reperfusion (I/R) injury is one of the leading causes of mortality following partial hepatectomy, liver transplantation, hypovolemic shock and trauma; however, effective therapeutic targets for the treatment of hepatic I/R injury are lacking. Recent studies have shown that diminazene aceturate (DIZE) has protective effects against inflammation, oxidative stress and cell death, which are the main pathogenetic mechanisms associated with hepatic I/R injury. However, the mechanistic effects DIZE exerts on hepatic I/R remain unknown. C57BL/6 male mice were pretreated with either 15 mg/kg DIZE or vehicle control (saline) and subjected to partial liver ischemia for 60 min. One day after induction of hepatic I/R, liver damage, inflammatory responses, oxidative stress and apoptosis were analyzed. By evaluating plasma alanine aminotransferase levels and histology, we found that DIZE treatment attenuated liver failure and was associated with a reduction in histologically-apparent liver damage. We also found that DIZE-treated mice had milder inflammatory responses, less reactive oxidative damage and less apoptosis following hepatic I/R compared to vehicle-treated mice. Taken together, our study demonstrates that DIZE protects against ischemic liver injury by attenuating inflammation and oxidative damage and may be a potential therapeutic agent for the prevention and treatment of ischemic liver failure.